1995
DOI: 10.1007/s002770050045
|View full text |Cite
|
Sign up to set email alerts
|

P53 Tumor suppressor gene in chronic myelogenous leukemia: a sequential study

Abstract: Loss of the p53 gene alleles was investigated in 26 patients with Ph+, BCR/ABL+ chronic myeloid leukemia (CML) by means of the polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) analysis using the restriction enzyme AccII. In all cases, peripheral blood and/or bone marrow samples were obtained at different times during the chronic phase of the disease and at blast crisis, and in some of them also at the accelerated phase. Of the 12 cases considered informative, 11 evolved into my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Survival mechanisms associated with p53 activation may be especially relevant because almost all CML-CP and about 70-85% of CML-BC cases are expected to retain wild-type p53. [76][77][78][79] It can be postulated that each type of neoplastic cell offers a particular environment in which p53 might generate different effects. For example, elevated expression of p53 in 32Dcl3 hematopoetic cell line transformed by v-ABL manifested a reduction in growth rate, while the v-SRC-transformed cells underwent differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Survival mechanisms associated with p53 activation may be especially relevant because almost all CML-CP and about 70-85% of CML-BC cases are expected to retain wild-type p53. [76][77][78][79] It can be postulated that each type of neoplastic cell offers a particular environment in which p53 might generate different effects. For example, elevated expression of p53 in 32Dcl3 hematopoetic cell line transformed by v-ABL manifested a reduction in growth rate, while the v-SRC-transformed cells underwent differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…P53 point mutations are generally associated with loss of the other P53 allele, through 17p deletion. In CML, as seen above, several case reports have suggested that loss of a P53 allele preceded the presence of a detectable P53 point mutation Rovira et al, 1995). In a large series of MALT lymphoma, of the 11 low-grade tumours which showed P53 abnormalities, only one showed the concomitance of P53 mutation and allele loss, whereas, in high-grade tumours, six of nine affected cases displayed both P53 mutation and allele loss (Du et al, 1995).…”
Section: P53 Mutations: An Early or Late Event In Haematological Malimentioning
confidence: 91%
“…Whilst structural alterations of p53 are very rare in the chronic phase of CML, they are detected in 25 ± 30% of CML blast crisis cases (Ahuja et al, 1989;Mashal et al, 1990;Prokocimer and Rotter, 1994). Although the majority of studies concentrate on p53 mutations, several reports have implicated a mere reduction in wild type (wt) p53 gene dosage as a factor of key importance for the development of the accelerated phase Nakai et al, 1992;Rovira et al, 1995). reported that the loss of a wtp53 allele preceded any p53 mutation and that the hemizygous wtp53 expression conferred a growth advantage on the cells.…”
Section: Introductionmentioning
confidence: 99%